Application of Audiovisual Media to Improve the Learning Outcomes of Islamic Education Students at SD Negeri 101109 Aek Badak - Masrini (Jurnal Pendidikan Profesi Guru, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using audiovisual. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this research is elementary school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that audiovisual can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of 42.19% in the pre-cycle, 63.37% in the first cycle and 87.72% in the second cycle. Thus, the use can be used as an alternative to improve student learning outcomes in Islamic religious education learning.